Fluxional Boron Clusters: From Theory to Reality - Pan, Sudip; Barroso, Jorge; Jalife, Said; Heine, Thomas; Asmis, Knut R.; Merino, Gabriel (Accounts of Chemical Research, 2019)
ConspectusIsolated boron clusters exhibit many intriguing properties, which have only recently been unfolding with the hand-in-hand advancement of state-of-the-art experimental and theoretical methods for the analyses of their electronic structure, chemical reactivity, and nuclear dynamics. A fascinating property that a number of these clusters display is fluxionality, a dynamical phenomenon associated with the delocalized nature of the chemical bonding and related to the continuous exchange between interatomic neighbors. The electron-deficient nature of boron is the driving force behind its extraordinary ability to form multicenter bonds, and this in turn leads to fluxional behavior only when an appropriate combination of topology and bonding is present. The first instance of fluxionality in boron clusters, the quasi-planar anion B19 -, was reported in 2010. The rotational barrier of the inner B6 unit spinning within the peripheral B13 ring can be overcome even at low temperature, mimicking the characteristic motion of a rotary internal combustion engine, and hence, B19 - was entitled a boron-based molecular Wankel engine. Shortly after that, it was found that other quasi-planar boron clusters, like B13 + and B18 2-, also exhibit an almost barrier-free rotation of internal planar moieties. The case of the B13 + cation is special because, on the one hand, it was chosen to examine the way to initiate, control, and direct the internal rotation using circularly polarized laser radiation, and on the other hand, the experimental manifestation of fluxionality was first established for this system through infrared experiments. Nevertheless, fluxional behavior is not limited to planar or pure boron clusters. Larger boron clusters, such as the fullerene-analogue borospherenes B40 and B39 -, are also predicted to show pronounced dynamical behavior that is related to the interconversion between six- and seven-membered rings. Be6B11 -, a triple-layer cluster, is another particularly interesting system since it exhibits multifold fluxionality consisting of the revolution of the outer boron ring around the Be6 core and the spinning of the two Be3 rings with respect to each other. The essential criteria for dynamical behavior in boron clusters are (1) the absence of a localized two-center, two-electron (2c-2e) bond between two molecular regions that tend to rotate with respect to each other, (2) the absence of steric hindrances for rotation and reorganization, and (3) retention of the delocalized electronic structure throughout the rotation/reorganization process. The fulfillment of the above three conditions ensures that low energy barriers will be associated with the rotation or reorganization of molecular moieties. The first two points can be illustrated from the facts that a single localized C-B σ bond in CB18 raises the rotational barrier by 27.0 kcal·mol-1 and the expansion of the outer ring by a single boron atom in moving from B12 + to B13 + lowers the rotational barrier by 7.5 kcal·mol-1. Alternatively, it is also possible to make a rigid boron cluster fluxional through doping, where the geometric and electronic changes caused by a suitable dopant, as in MB12 - (M = Co, Rh, Ir) and B10Ca, reduce the corresponding rotational barriers enough to achieve fluxionality. At present, there are 13 pure boron clusters (B11 -/0/+, B13 +/0/-, B15 +/0/-, B18 2-, B19 -, and B20 -/2-) and eight metal-doped boron clusters (B10Ca, NiB11 -, [B2-Ta@B18]-, Be6B11 -, Be6B10 2-, and MB18 - (M = K, Rb, Cs)) that have sufficiently small rotational barriers (less than ∼1.5 kcal·mol-1) to exhibit fluxional behavior at low temperature. Some of the other reported boron clusters show more sizable barriers, and their dynamical behavior is manifested only at elevated temperatures. The research on such systems is driven by the notion that it ultimately will pave the way for the development of light-harvesting boron-based nanomotors/machines and robots, a reality that may not be that far away!.
CRIS-Team Scopus Importer:2022-04-14